2005
DOI: 10.1590/s0034-89102005000500004
|View full text |Cite
|
Sign up to set email alerts
|

Crenças e atitudes educativas dos pais e problemas de saúde mental em escolares

Abstract: Objective To verify the prevalence and identify the risk factors related to mental health problems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
34

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 15 publications
2
17
0
34
Order By: Relevance
“…The 10.7% prevalence of ADHD obtained through the information provided by the parents/guardians is close to the one found in national and international screening studies. 21,35 The absence of a statistically signifi cant difference between sexes and the increase in ADHD with age are not frequently found in the literature. Authors have shown that the type of informant (parents would tend to overvalue the hyperactive behavior of girls) and the subtypes of ADHD (parents tend to point more symptoms of hyperactivity-impulsivity in younger children) infl uence gender differences, and can be responsible for the wide variety of results.…”
Section: Discussionmentioning
confidence: 99%
“…The 10.7% prevalence of ADHD obtained through the information provided by the parents/guardians is close to the one found in national and international screening studies. 21,35 The absence of a statistically signifi cant difference between sexes and the increase in ADHD with age are not frequently found in the literature. Authors have shown that the type of informant (parents would tend to overvalue the hyperactive behavior of girls) and the subtypes of ADHD (parents tend to point more symptoms of hyperactivity-impulsivity in younger children) infl uence gender differences, and can be responsible for the wide variety of results.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à angústia, G1 a experienciaria num nível mais elevado que G2, apresentando assim um estado emocional mais fragilizado, com sentimentos de depressão, frustração, tristeza, preocupação, confusão, desordem, baixa auto-estima e raiva (Milner, 1986). Investigações têm demonstrado que esses fatores se constituem em risco para o abuso físico (De Antoni et al, 2007;McElroy & Rodriguez, 2008;Palusci et al, 2005;Pittman & Buckley, 2006;Vitolo et al, 2005;Woodward & Fergusson, 2002) quando na presença de fatores de natureza cognitiva (Francis & Wolfe, 2008;Rodriguez & Richardson, 2007), e que déficits no controle das emoções é um problema vivido por cuidadores com histórico de abuso (Hien et al, 2010;Mammen et al, 2002).…”
Section: Discussionunclassified
“…Os estudos de Krug et al 10 e Vitolo et al 11 indicaram alguns aspectos que tornam a criança e o adolescente mais vulneráveis a terem problemas no desenvolvimento socioemocional. Os achados revelaram a influência de fatores individuais da criança, como sexo, idade e características psicológicas; fatores familiares, história de problemas de saúde mental, especialmente materna, problemas de álcool/ drogas, violência física, psicológica e sexual, violência entre os pais, perdas por morte, separação dos pais; e fatores socioculturais como a pobreza, violência no contexto social e apoio social.…”
Section: Introductionunclassified